A FACTORS ASSOCIATED WITH THE OCCURRENCE OF GASTROESOPHAGEAL REFLUX DISEASE (GERD) IN STUDENTS: Faktor Yang Berhubungan Terhadap Kejadian Gastroesophageal Reflux Disease (GERD) Pada Mahasiswa - Siregar, Santy Deasy; Hulu, Victor Trismanjaya; Lase, Dian Veronika (Universitas Airlangga, 2025)
Background: Gastroesophageal Reflux Disease (GERD) cannot be left without action because it can cause severe stomach irritation in the long term, leading to stomach ulcers and infection. Purpose: This study aims to analyze factors related to the incidence of Gastroesophageal Reflux Disease (GERD) in students. Methods: This type of research in analytical survey research. The design of this research is case control. The population in this study were students of Universitas Prima Indonesia, class of 2021, in the public health study program and the information systems study program, totaling 1,473 students. The sample in this stufy was a portion of the student population which was divided into case and control groups. Data analysis was carried out using the Chi-square test to determine the description and relationship of risk factors with the incidence of GERD. Results: The result showed that the eating habits variable (p = 0,000; OR = 19,12; 95% CI = 6,376-57,369), coffee consumption variable (p = 0,001; OR = 4,93; 95% CI = 1,986-12,262), stress level variable (p = 0,001; OR = 4,52; 95% CI = 1,952-10,508), and body mass index variable (p = 0,000; OR = 5,63; 95% CI = 2,362-13,420) has a significant relationship with the incidence of GERD in students. Conclusion: reducing the consumption of ready-to-eat food and reducing the lifestyle of modern society which consumes excessive coffee and doing positive things to maintain stress levels are very important things to increase public awareness in order to minimize the risk of GERD.